2011
DOI: 10.1093/cid/cir808
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Epidemiology of Melioidosis Pneumonia: Results From a 21-Year Study and Review of the Literature

Abstract: Melioidosis pneumonia is often a rapidly progressive illness with high mortality, particularly among those with multilobar disease. Risk factors have been identified, and early diagnosis and treatment should be priorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
137
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(149 citation statements)
references
References 32 publications
10
137
0
2
Order By: Relevance
“…This study also showed that three factors associated with death included pulmonary presentation, blood urea nitrogen level, and white blood cell count. Pulmonary presentation had the highest adjusted OR among all predictors and was also previously reported as the most common presentation of melioidosis [12,13]. Pulmonary presentation was found in 51% of patients who had melioidosis [5,15].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This study also showed that three factors associated with death included pulmonary presentation, blood urea nitrogen level, and white blood cell count. Pulmonary presentation had the highest adjusted OR among all predictors and was also previously reported as the most common presentation of melioidosis [12,13]. Pulmonary presentation was found in 51% of patients who had melioidosis [5,15].…”
Section: Discussionsupporting
confidence: 54%
“…Seventy-one percent of patients who died from septicemic melioidosis in this study also had pulmonary problems, while only 27.27% of patients who survived had pulmonary problems (Table 1). Patients with acute pneumonia from melioidosis had a high risk of septic shock, acute respiratory distress syndrome, and death [6,13].…”
Section: Discussionmentioning
confidence: 99%
“…Melioidosis mainly occurs in the rainy season. 6 The bacteria reach the body by inhalation or ingestion of contaminated water or food. Peak incidence occurs in the 4 and 5 decade and studies from different parts of world have shown a distinct male predominance, that is 69%, 75%, and 62% of patients, respectively from Australia, 6 Malaysia, 7 and Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…6 The bacteria reach the body by inhalation or ingestion of contaminated water or food. Peak incidence occurs in the 4 and 5 decade and studies from different parts of world have shown a distinct male predominance, that is 69%, 75%, and 62% of patients, respectively from Australia, 6 Malaysia, 7 and Thailand. 8 Although healthy people may get melioidosis, the major risk factors include diabetes (present in 23-60% of patients), heavy alcohol use (in 12-39%), chronic pulmonary disease (in 12-27%), chronic renal disease (in 10-27%), thalassemia (in 7%), glucocorticoid therapy (in <5%), and cancer (in <5%).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] The increased incidence of melioidosis generally arises after heavy monsoonal rains, cyclones, or typhoons have occurred, leading to a shift toward the inhalation of B. pseudomallei that is significantly correlated with pneumonia, bacteremia, septic shock, and a high mortality rate. [8][9][10] The extraordinary survival period of B. pseudomallei, which ranges from months to years in the endemic regions during the dry season and in a laboratory setting, highlights its persistence, adaptability, and ability to survive. [11][12][13] An examination of B. pseudomallei maintained in distilled water at 25°C for 16 years provided evidence of its ability to survive under extreme conditions.…”
Section: Introductionmentioning
confidence: 99%